Metatextual reconstruction of Chineseness as a site of constellation in Tash Aw’s literary representation - Su Jianbo; Ruzy Suliza Hashim (Penerbit Universiti Kebangsaan Malaysia, 2023)
The notion of Chineseness has been contested and negotiated for decades due to the cultural and geopolitical contingencies and disjunctures of disparate lived experiences between the mainland and cross-border Chinese communities. Under these circumstances, the polemic has never ceased to be settled, with the major focus on the tensions between state-led nationalism and diasporic transnationalism. Despite the fact that prior studies have proposed a variety of approaches to avoid any effort at blanket integration or radical exclusion, both sides are inevitably bound inside the habitualized ideological apparatus, locking the discussion in an endless loop of essentialism. To transcend the epistemic gridlock, this article, based on Tash Aw’s selected literary works, postulates an experimental praxis for rewriting composite Chineseness via metatextual reconstruction. Through the strategic juxtaposition and comparison of fluidly correlated narratives, the structural flaw built within the theoretical terrain of Chineseness would possibly be bridged, which foreshadows a constellation of multilayered Chineseness to come